PrDA1-1 and its interacting proteins PrTCP1/PrTCP9 in flare tree peony affect yield by regulating seed weight and number - Chunyan He; Fangyun Cheng (Journal of Integrative Agriculture, 2025)
Tree peony is an emerging woody oilseed crop that has the potential to help meet the growing demand for edible oil and biofuel, and breeding high-yield varieties is the key to increasing production. The DA1 gene regulates seed weight and number and effectively improves crop yield, although its function in tree peonies has not yet been reported. In this study, three PrDA1 genes were first identified in the whole genome of ‘Jing Hong’ flare tree peony (Paeonia rockii). PrDA1-1 is homologous to AtDA1 and contains three types of conserved structural domains: UIM (ubiquitin-interacting motif), LIM (Lin11, Isl-1, and Mec-3), and DA-like. PrDA1-1 was strongly expressed during both the early and late stages of seed development, and its constitutive expression in Arabidopsis reduced seed number but increased seed weight, which ultimately led to a reduction in yield. PrDA1-1 was found to interact with PrTCP1/PrTCP9 in yeast and plants, and the constitutive expression of PrTCP1/PrTCP9 in Arabidopsis increased seed weight and number, which resulted in higher yield. Since this study showed that PrDA1-1 and PrTCP1/PrTCP9 regulate seed weight and number to affect yield, these new genetic resources will help to improve the seed yield of tree peonies.